Diagnosis and management of lipodystrophy: a practical update. (April 2014) - Stears, Anna; Hames, Catherine
Lipodystrophy is a group of rare conditions characterized by partial or complete loss of subcutaneous adipose tissue. Lipodystrophy is associated with metabolic derangements including severe insulin resistance, diabetes, hypertriglyceridemia, pancreatitis, nonalcoholic fatty liver disease and, in females, hyperandrogenism, polycystic ovarian syndrome and subfertility. The underlying cause may be genetic or acquired. Patients may present in childhood or adulthood. The diagnosis is frequently delayed, especially in partial lipodystrophy. Avoidance of excess dietary energy intake, despite the often lean appearance of the patient, is the current mainstay of treatment, aiming to avoid short- and long-term complications, while allowing normal growth in children. Early involvement of a specialized multidisciplinary team in the diagnosis and management of patients with lipodystrophy may enable evidence-based management guidelines to be developed. The timely diagnosis of lipodystrophy is becoming more important as novel treatment options such as recombinant methionyl human leptin therapy has recently been approved for use in some patients.